2005
DOI: 10.1016/j.amjhyper.2005.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness and Plasma Creatinine in Untreated Hypertensive Patients

Abstract: Background: Increased arterial stiffness is a common feature of hypertensive subjects with renal failure, independently of age, office blood pressure (BP), and traditional cardiovascular risk factors including atherosclerosis but not diabetes mellitus. Recently a reduction in creatinine clearance was shown to be associated with increased arterial stiffness in patients with normal or elevated BP and mild renal failure, and the association was noted to be stronger in subjects Ͻ55 years of age. We wanted to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 24 publications
2
19
0
1
Order By: Relevance
“…Moreover, recent studies have suggested an association between impaired renal function and decreased arterial stiffness in essential hypertensive patients. [11][12][13]20,21 In the present study, AASI and 24-h PP were inversely correlated with eGFR-MDRD and eGFR-EPI, independent of other cardiovascular risk factors, such as MBP. However, after adjusting for all the potential confounders, including AASI, 24-h PP and other risk factors, AASI (P¼0.053), but not 24-h PP (P¼0.081), was independently related to eGFR-EPI.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Moreover, recent studies have suggested an association between impaired renal function and decreased arterial stiffness in essential hypertensive patients. [11][12][13]20,21 In the present study, AASI and 24-h PP were inversely correlated with eGFR-MDRD and eGFR-EPI, independent of other cardiovascular risk factors, such as MBP. However, after adjusting for all the potential confounders, including AASI, 24-h PP and other risk factors, AASI (P¼0.053), but not 24-h PP (P¼0.081), was independently related to eGFR-EPI.…”
Section: Discussionmentioning
confidence: 62%
“…9 Alteration of arterial stiffness, a subclinical sign of TOD in hypertension, has been reported to be correlated with renal function within the normal range 10 or in renal dysfunction. [11][12][13][14][15][16][17] As a surrogate index of arterial stiffness, PP is correlated with early signs of renal dysfunction. 18,19 Similar to PP, AASI is also associated with TOD 20 and renal abnormalities 21,22 in untreated patients with primary hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…However, given the relatively weak association between GFR and upper-limb PWV, small sample size may have precluded the demonstration of a significant association in that study. In 263 hypertensive subjects with normal or mildly reduced GFR, Gosse and Safar 12 found a positive relation between plasma creatinine and QKD interval. Although correlated with more direct measures of arterial stiffness, 27 the QKD interval depends on several other variables, including ventricular activation and body height, and represents a cumulative measure of aortic and upper-limb PWV velocity, so the effects of renal function on central and peripheral stiffness could not be distinguished in that article.…”
Section: Kidney Disease and Peripheral Muscular Artery Stiffnessmentioning
confidence: 99%
“…10 Among people with mild renal failure, arterial stiffness is directly related to GFR. 11 In hypertensive patients, Gosse and Safar 12 have observed that the time interval between the R wave on the ECG and the last Korotkoff sound heard over the brachial artery when measuring blood pressure ([BP] named the QKD interval) is directly related to estimated GFR. QKD interval is considered an approximate measure of arterial transit time and, therefore, an estimate of arterial compliance, and that study suggests a relation between arterial stiffness and reduced GFR even in uncomplicated patients with essential hypertension.…”
mentioning
confidence: 99%
“…Aortic stiffening causes increased systolic blood pressure (BP; SBP) and widened pulse pressure (PP), both factors associated in longitudinal studies with increased rate of decline of renal function. 6,7 In addition, aortic stiffening results in loss of the dampening of ventricular ejection and could lead to increased transmission of these pressure changes to organ microvasculature. 8 The renal microcirculation may be particularly affected because the low resistance provided by the renal afferent arterioles means that the glomerular capillaries are exposed to potentially damaging pulsatile pressures, which may result in a permanent reduction in glomerular filtration rate (GFR).…”
mentioning
confidence: 99%